2009
DOI: 10.1111/j.1365-2044.2008.05874.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring neuromuscular block: an update

Abstract: SummaryThe first part of this article presents an update of the basic considerations of neuromuscular monitoring. It emphasises the need to assure supramaximal stimulation, to place the stimulating electrodes correctly and to use appropriate sites for nerve stimulation as well as appropriate stimulation patterns. The second part focuses on current developments and ongoing discussion. The authors describe the performance of acceleromyography and the need for initial calibration when using these quantitative dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 31 publications
1
34
1
8
Order By: Relevance
“…25 The twitch response is decreased 2% to 10% per degree Celsius reduction in the muscle temperature. In patients given NMBAs, pharmacokinetic changes occur because of the effects of hypothermia on drug disposition.…”
Section: Hypothermiamentioning
confidence: 98%
See 1 more Smart Citation
“…25 The twitch response is decreased 2% to 10% per degree Celsius reduction in the muscle temperature. In patients given NMBAs, pharmacokinetic changes occur because of the effects of hypothermia on drug disposition.…”
Section: Hypothermiamentioning
confidence: 98%
“…Another concern is the lack of consensus about the TOF ratio needed to exclude clinically important RNMB. 23,25 TOF is an assessment that involves stimulation of peripheral nerves. A series of 4 light shocks are applied to a peripheral nerve, and visual observation of the muscular response to each shock is used to measure the degree of neuromuscular blockade.…”
Section: Clinical Monitoring Of Neuromuscular Blockadementioning
confidence: 99%
“…Monitoring myorelaxation has long been shown to be a factor of quality of anaesthesia as it enables adequate titration during surgery and security when weaning ventilation and extubating patients [16][17][18]. Myolexation monitoring relies on electrical stimulations of the ulnar nerve at the wrist or of the palpebral orbicular muscle: results are expressed as a percentage of muscular response, with known thresholds (targets) for surgery and extubation [19]. In current practice, various types of electrical stimulations can be used.…”
Section: Monitoring Myorelaxationmentioning
confidence: 99%
“…In contrast, techniques using acceleromyography are suitable for clinical practice. Issues around calibration, drift and 'normalisation' have been debated [3], but a systematic review concluded that '(acceleromyography) improves detection of postoperative residual paralysis and that recovery of TOF ratio to unity indicates, with a high predictive value, recovery of pulmonary and upper airway function from residual neuromuscular blockade' [4]. Movement of the stimulated limb will affect calibration of the device for twitch height measurement.…”
Section: Universal Neuromuscular Blockade Monitoring -A Replymentioning
confidence: 99%